Comunidade, enraizamento, socioambiente: entre poética e política - Omar Ardans (Ciências Sociais Unisinos)
The text reflects upon the relationships between the concepts of community and social- environmental space through the concept of rooting, showing the historical and cultural relationship between poetry and politics, considering the effects of an unrestrained and uprooting globalization.